Water Stress Inhibits Germination While Maintaining Embryo Viability of Subtropical Wetland Seeds: A Functional Approach With Phylogenetic Contrasts - Bhatt, Arvind; Daibes, L. Felipe; Gallacher, David J.; Jarma-Orozco, Alfredo; Pompelli, Marcelo F. (Frontiers in Plant Science, 2022)
Wetland species commonly exhibit a range of strategies to cope with water stress, either through drought tolerance or through avoidance of the period of limited water availability. Natural populations provide a genetic resource for ecological remediation and may also have direct economic value. We investigated the effects of drought stress on the seed germination of wetland species. Nineteen species were germinated in four concentrations of polyethylene glycol 6000 (PEG) and were evaluated daily (12-h light photoperiod) or after 35 days (continuous darkness) to determine seed germination under water stress. Germination percentage decreased with an increase in polyethylene glycol 6000 (PEG) concentration, but species’ germination response to PEG concentration varied significantly. Seeds recovered their germinability after the alleviation of water stress, but the extent of recovery was species-dependent.